PENGARUH LINGKUNGAN KERJA, MOTIVASI, DAN KOMPENSASI TERHADAP KEPUASAN KERJA UNTUK MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN PADA PT. RAYA AZURA PERSADA - Agustina Mogi, Sidik Priadana, Azhar Affandi, Umi Narimawati (LPPM University 17 Agustus 1945 Samarinda, 2022)
Determining the effect of the Work-Environment, Motivation and Compensations on Job-Satisfaction for this study to improve work productivity at PT. Raya Azura Persada.A quantitative-research is research that is elected by the researcher. Saturated sample is used for sampling from the total population, namely all employees who work at PT. Raya Azura Persada. A questionnaire is used to collect data.Based on data, we can conclude that there is significance (0,045) between the Work-Environment (variable-X1). There is no significance (>0,05) between Motivation & Compensation on Job-Satisfaction (variable-Y). Aside from that there is no influence of Work-Environment (variable-X1), Motivation (variable-X2) & Compensation (variable-X3) for work productivity (variable-Z) indicated by the value of significance > 0.05.